The anthropological construction for the dramatic character in television series (Al-Academy, 2025)
Anthropology is a social science concerned with studying the human personality as a complex and multidimensional being. It examines it through several aspects, such as biological, cultural, social, and symbolic. This science emerged out of a desire to recognize and understand human diversity, not only at the level of customs and traditions, but also in ways of thinking, social and ethical value systems, and the various lifestyles that characterize human societies. The importance of anthropology lies in its great ability to reveal and present an accurate and comprehensive picture of the human personality, making it one of the most important sciences active in building an open-minded awareness capable of studying cultural pluralism, which contributes to areas of creativity, particularly in the field of fine arts. Anthropology is concerned with studying humans comprehensively from multiple angles, starting with their physical structure, moving on to their behavioral makeup, reaching their culture and history, the societal environment in which they live and grow, and everything surrounding them that contributes to their personal human structure. At the heart of every dramatic work of art are primary and secondary characters, and these characters are not created in a vacuum. Rather, it is a visual and vocal reflection of a specific society and a certain culture, in which ideas and beliefs are manifested that were formed in studied social and historical contexts. Here, the importance of anthropology appears through its dedication by the creator of the artwork (the director) because it helps him understand how this character is formed, what motivates it, and why it behaves in this way, by looking at its cultural background and the societal structure to which it belongs. Here, the deep relationship between anthropology as a science and the visual dramatic arts (television drama).